Designing Learning Media Based on ICT for Student’s Reading Skills of Tenth Grade SMK TI Annajiyyah Bahrul Ulum - Ulfa Wulan Agustina; Mukhlisoh, Nani; Nur, Luluk Choirun Nisak; Hidayat, Rohmat (Institut Agama Islam Negeri Ponorogo, 2024)
This study aims to design MRELISH (Mukhlisoh Reading English) based on ICT, to improve the tenth-grade Vocational High School students’ interest in English learning, especially reading skill. This study used Research & Development (RND) method with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. In the Analyze phase, the researchers used two instruments, those are interviews and questionnaires. The results from interview data stated that MRELISH English teachers approved MRELISH media to be designed and developed. while the results of the students’ questionnaire stated that 69% of the total number of students agreed that MRELISH media was developed and applied in their English learning. In the Development and Implementation phases, the researchers used some instruments to collect data: interviews, questionnaires, observations, and documentation. The result of questionnaires from the material validation was 82% in the “very good” category and the result of the media validation was 92% in the “very good” category. After being implemented to students, the final result of the implementation was 84% which was categorized as “very good”. Based on those results, it can be concluded that MRELISH (Mukhlisoh Reading English) application was suitable to use in English learning to improve student’s reading skills in Vocational High School.